Mad men. Season five [videorecording (DVD)] - Abraham, Phil; Moss, Elisabeth, 1982-; Slattery, John, 1962-; Hamm, Jon, 1971- (Lionsgate, 2012)
Mad Men is back and plunges into the seductive and intriguing world of Sterling Cooper Draper Pryce. Jon Hamm and the rest of the award-winning cast continue to mesmerize as they adapt .to changing times, social revolution, and a radical world. Lust is back. Adultery is back. Deception is back.